Punitive benefit sanctions, welfare conditionality and the social abuse of unemployed people in Britain: transforming claimants into offenders? - Fletcher, Del (2020)
A defining feature of U.K. welfare reform since 2010 has been the concerted move towards greater compulsion and sanctioning, which has been interpreted by some social policy scholars as punitive and cruel. In this article, we borrow concepts from criminology and sociology to develop new interpretations of welfare conditionality. Based on data from a major Economic and Social Research Council‐funded qualitative longitudinal study (2014–2019), we document the suffering that unemployed claimants experienced because of harsh conditionality. We find that punitive welfare conditionality often caused symbolic and material suffering and sometimes had life‐threatening effects. We argue that a wide range of suffering induced by welfare conditionality can be understood as ‘social abuse’, including the demoralisation of the futile job‐search treadwheel and the self‐administered surveillance of the Universal Jobmatch panopticon. We identify a range of active claimant responses to state perpetrated harm, including acquiescence, adaptation, resistance, and disengagement. We conclude that punitive post‐2010 unemployment correction can be seen as a reinvention of failed historic forms of punishment for offenders